Unveiling the role of K2NiF4-Structure Pr4Ni3O10+ surface coverage in boosting oxygen permeation and suppressing membrane degradation - Saher S.; Tan C.Y.; Ramesh S.; Yap B.K.; Ong B.H.; Mo K.H.; Al-Furjan M.S.H. (Elsevier B.V., 2025)
To probe the oxygen flux over an extended period of 1000 h, oxygen permeation measurements are performed at 700 C for La0.6Sr0.4Co0.2Fe0.8O3- (LSCF) coated with K2NiF4-structure Pr4Ni3O10+ (PNO) while varying surface coverage. The optimization of PNO surface coverage, thickness, and porosity over LSCF involves the application of ultrasonic vibration of the nozzle chamber within the range of 40 kHz to 180 kHz. This is coupled with the adjustment of the gap between the nozzle exit and substrate surface, ranging from 2 cm to 9 cm. The results indicate that the PNO coating facilitated an increase in oxygen permeation and hindered the formation of secondary phases on the surface, known to cause degradation over time. When compared to bare LSCF, a minimal increase of 8 % in oxygen permeation is observed for the coated sample with a PNO loading content of 7.21 m, denoted as PNO1. Conversely, the most significant enhancement of 74 % is seen for the loading content of 5.06 m, referred to as PNO5. The LSCF membrane experiences a degradation of oxygen flux by 11 % after prolonged operation, significantly surpassing the mere 2.1 % degradation observed for the best-performing PNO5 membrane. This improvement is achieved by suppressing the segregated phases of SrO and CoFe2O4 on the surface. The observed enhancement in oxygen flux is attributed to the optimal surface coverage of the PNO-coated particulate, which increases the number of active sites for the oxygen reduction reaction (ORR). ? 2023